Kultura jako przedmiot badań. O możliwości systematyki w obszarze "critical culture studies" - Pępiak, Ewa (Er(r)go. Teoria - Literatura - Kultura, 2005)
Ewa Pępiak Culture as an Object of Research. On the Possibility of Systematization in Critical Culture Studies The article discusses modern cultural dominants and the ways of describing culture in the context of cultural turn in humanities and the rise of critical cultural studies.